The effect of different doses of Tarantula-Logoplex® on oxidative status and biochemical parameters in Japanese quails (Indian Journal of Traditional Knowledge (IJTK), 2024)
Two commercial forms of Tarantula cubensis (TC) extract are used as homeopathic agents in veterinary medicine. These are Tarantula-Logoplex® (TL) and Theranekron® (THR). This study aims to evaluate the effect of TL on albumin (ALB), aspartate aminotransferase (AST), alkaline phosphatase (ALP), cholesterol (CHO), creatinine (CRE), blood urea nitrogen (BUN), malondialdehyde (MDA), superoxide dismutase (SOD) and catalase (CAT) values in healthy quails. A total of 24 Japanese quails were divided into 2 equal groups TL0.6 (n: 12, 0.6 mL/animal, IM) and TL0.8 (n: 12, 0.8 mL/animal, IM). Before the application, control blood was taken from the medial metatarsal vein of 6 quails in each group. Blood was drawn from the medial metatarsal vein at the 2nd, 4th, 8th, 24th and 48th hours after administration (6 quails were used at each sampling time). Animals were euthanized by decapitation after blood collection at the last sampling time. ALB, AST, ALP, CHO, CRE and BUN levels were measured with an auto-analyzer, whereas MDA, SOD and CAT values were determined with an ELISA reader. TL caused increases in hepatic damage markers (AST, ALP) and fluctuations in oxidative stress markers (MDA, SOD). Due to the increase in AST and ALP values in Japanese quail, it is recommended to be careful when using TL at these doses.